BLUE ECONOMY POLICY INCLUSION AND SOCIAL CAPITAL TRANSFORMATION OF FISHING COMMUNITIES IN BIAK NUMFOR REGENCY - Iriawan, Hermanu; Ahmad, Busyairi (Gema Kampus IISIP YAPIS Biak, 2026)
This study aims to analyze blue economy policy inclusion and social capital transformation among fishing communities in Biak Numfor Regency. The issue is significant because Biak Numfor has substantial marine and fisheries potential, yet the implementation of blue economy policies at the local level often encounters challenges related to unequal access to information, limited institutional capacity, uneven participation, and insufficient strengthening of coastal community networks. Globally, the blue economy is understood as the sustainable use of ocean resources for economic growth, improved livelihoods, and marine ecosystem protection. In Indonesia, the Ministry of Marine Affairs and Fisheries promotes blue economy policies through measured fishing, sustainable aquaculture, coastal management, and marine plastic waste reduction. This study employs a descriptive qualitative approach using in-depth interviews, field observation, and documentation. Data were analyzed through data reduction, data display, and conclusion drawing. The findings reveal that blue economy policy inclusion has not been fully equitable at the level of fishing communities, yet it has stimulated social capital transformation in the forms of strengthened trust, work solidarity, economic networks, and collective participation. However, these transformations remain constrained by limited market access, inadequate fisheries infrastructure, and the lack of integration between local institutions and sectoral policies. This study recommends a participatory, community-based, and socio-culturally sensitive blue economy governance model for fishing communities in Biak Numfor Regency.